Implementasi Kegiatan Muhadoroh dalam Meningkatkan Kemampuan Public Speaking Santri Rumah Qur’an Desa Tajurhalang Kabupaten Bogor - Miftahudin, Mufti; Nawawi, M Kholil; Arif, Suyud (At-Tadris: Journal of Islamic Education, 2025)
This study examines the implementation of the Muhadoroh activity in enhancing the public speaking skills of students at Rumah Qur’an Desa Tajurhalang, Bogor Regency. The Muhadoroh activity, held regularly each week, offers students opportunities to practice public speaking by delivering short speeches, sermons, and leading prayers in front of their peers. This research uses a qualitative approach with descriptive analysis to explore the implementation of Muhadoroh and its impact on the students' public speaking abilities. The findings show that prior to participating in Muhadoroh, most students experienced anxiety and lacked confidence when speaking in public. However, with consistent guidance from instructors, students demonstrated significant improvement in confidence, structuring their material, and speaking clearly. Additionally, the activity had a positive impact on their social skills and self-assurance. Despite these improvements, several challenges were identified, including limited facilities, uneven skill levels among students, and distractions from gadget usage at home. To optimize the results, it is recommended to strengthen communication between Rumah Qur’an and parents, increase the variety of training methods, and create a more supportive environment at home for practicing. This study highlights the importance of Muhadoroh in developing essential public speaking skills for students, which are valuable in both their da’wah and social engagements.